2015
DOI: 10.1038/nrdp.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Spina bifida

Abstract: Spina bifida is a birth defect in which the vertebral column is open (bifid), often with spinal cord involvement. Clinically most significant is myelomeningocele (MMC; open spina bifida) in which the spinal neural tube fails to close during embryonic development. The exposed neural tissue degenerates in utero, resulting in neurological deficit that varies with level of the lesion. Occurring in around 1 per 1000 births worldwide, MMC is one of the commonest congenital malformations, yet its causation is largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
463
1
37

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(507 citation statements)
references
References 225 publications
(220 reference statements)
6
463
1
37
Order By: Relevance
“…In developing fetuses, it creates a disposition to birth defects known as neural tube defects, which involve failure of neural tube closure early in pregnancy. Outcomes range in severity from anencephaly, causing fetal loss, to spina bifida with partial leg paralysis (Copp et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In developing fetuses, it creates a disposition to birth defects known as neural tube defects, which involve failure of neural tube closure early in pregnancy. Outcomes range in severity from anencephaly, causing fetal loss, to spina bifida with partial leg paralysis (Copp et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the cerebellar height from ODL demonstrated a clear difference between fetuses with MMC and those without MMC. The MOMS study demonstrated certain benefits of MMC repair, for as long the surgery was done prior to 26 weeks and in specialized centers . Thus, spina bifida should be accurately and timely diagnosed, so that patients have an option of choosing fetal surgery and can be referred.…”
Section: Discussionmentioning
confidence: 99%
“…There is marked geographic variation, but the average worldwide prevalence of neural tube defects has been estimated at one case per 1000 births 1. Even with prompt surgical repair of the spinal lesion, most infants will have residual neurological deficit, bowel and bladder dysfunction.…”
Section: Introductionmentioning
confidence: 99%